L’activité de l’encadrant : savoir adopter la perspective de l’activité d’autrui - Hervé de Bisschop; Jean-François Métral (Activités, 2023)
As an activity “of intervention on the activity of others” (Barbier, 2011, p. 62), when conceived as the experience that emerges from the dynamic coupling between an actor and his/her environment in a situation of facilitating a work group, the manager’s activity remains largely hidden to an outside observer. To understand it, one therefore requires methods that reveal the way in which the managers construct a point of view on the activity of those they are supervising. With a view to achieving such understanding, this research proposes to document the variables of the situation relating to the activity of the supervisees, to their states and to their evolution according to the situational transformations that the manager takes into account in order to know, do and control what is to be done (Tourmen, 2014). To this end, our research examines the experience of army cadets during a training course. The results show how, in order to deploy their activity, the managers combine two simultaneous perspectives on the situation: their own; the one they attribute to others and which they infer from combinations of information gathered about the group and its members, the environment, the performance of the task and their own activity (what they think, do and feel). This research sheds additional light on what the activity-based approach can contribute to the understanding of a complex activity such as that of the managers, in particular by documenting it not only from the description of what they do (Mintzberg, 1984) but also from what they live and experience within themselves and with others. It leads to a range of proposals for the training of future managers.